Medical grade antimicrobial flexible circuit board
Patent Information
- Application Number
- CN202611256795.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-13
AI Technical Summary
第一,监测手段单一、空间分辨率低
(1)多功能集成:本发明通过在气凝胶层中或层间设置抗菌功能,使柔性线路板同时具备隔热和抗菌双重功能,无需额外增加抗菌涂层,减少了整体厚度,保持了柔性线路板的柔韧性。
Smart Images

Figure CN122909766A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of flexible electronics technology, specifically to a medical-grade antibacterial flexible circuit board. Background Technology
[0002] Aquifer thermal energy storage technology, which stores heat energy generated from summer waste heat or renewable energy sources by injecting it into underground aquifers for later use during winter heating, is an important way to achieve low-carbon building energy systems. The sustainable operation of aquifer thermal storage systems depends on high-resolution monitoring of underground thermodynamic and hydraulic processes, especially heat plume transport, groundwater flow dynamics, and operational disturbances during injection and extraction.
[0003] However, existing aquifer thermal storage technologies still have the following shortcomings: First, the monitoring methods are limited and have low spatial resolution. Traditional monitoring methods can only provide sparse spatial information, making it difficult to comprehensively characterize the key behavioral features of aquifer thermal storage systems. Existing technologies mostly only monitor single points of the temperature or pressure fields, lacking the ability to monitor the multi-field coupling of temperature (T), seepage field (H), and stress field (M) in real time, and thus cannot accurately capture the coordinated evolution of multiple physical fields during thermal storage.
[0004] Second, there is a lack of multi-field coupled predictive computational models. Existing systems fail to effectively integrate real-time monitoring data with multi-field coupled numerical models, making it impossible to predict and warn of key indicators such as temperature field evolution, pressure transfer, and thermal breakthrough in the thermal storage process. With the rapid development of wearable devices, flexible displays, medical devices, and aerospace, the application of flexible printed circuit boards (FPCs) is becoming increasingly widespread. Due to their advantages such as bendability, light weight, and small size, flexible printed circuit boards play an irreplaceable role in confined spaces and dynamic bending scenarios.
[0005] However, existing technologies have the following shortcomings: (1) Aerogel insulation layer has a single function, only having heat insulation or sound absorption functions, and lacks antibacterial properties; (2) In scenarios where heat insulation and antibacterial functions need to be achieved simultaneously, the existing solutions usually involve simply stacking the antibacterial coating with the aerogel layer, which results in an increase in overall thickness and a decrease in flexibility. (3) When the antibacterial coating is directly applied to the surface of the aerogel, the bonding strength between the antibacterial particles and the aerogel is insufficient and they are easy to fall off. (4) There is a lack of effective solutions for scenarios where the thickness of aerogel needs to be precisely controlled in a specific area to meet bending requirements.
[0006] To address the above problems, this invention provides a flexible circuit board with both heat insulation and antibacterial functions, and a method for its preparation.
[0007] To address the aforementioned issues, this invention provides a medical-grade antibacterial flexible circuit board that enables coordinated operation of multi-field real-time monitoring, intelligent predictive calculation, and automatic injection control. Summary of the Invention
[0008] In view of this, a medical-grade antibacterial flexible circuit board is provided. The flexible circuit board has antibacterial function in the aerogel insulation layer or between the layers. At the same time, the thickness of the aerogel can be precisely controlled according to the needs of the bending area, so as to achieve antibacterial function and bending reliability while ensuring thermal insulation performance.
[0009] For the above purposes, one or more embodiments of this specification provide a medical-grade antibacterial flexible circuit board, comprising: Flexible circuit board substrate; At least one aerogel layer is disposed on the surface of the flexible circuit board substrate, and the aerogel layer serves as a heat insulation separation layer. LED beads or heating electronic components disposed on the flexible circuit board substrate, wherein the aerogel layer is disposed around or adjacent to the area where the LED beads or heating electronic components are located. An antibacterial functional structure is disposed in or between the aerogel layers; The flexible circuit board has a bending region and a non-bending region, and the thickness of the aerogel layer in the bending region is less than the thickness of the aerogel layer in the non-bending region.
[0010] The substrate is made of one or more of medical-grade polyimide, liquid crystal polymer, and polyethylene terephthalate, and the biocompatibility level of the substrate meets the requirements of USP Class VI or ISO 10993 standards; the matrix material of the aerogel layer is made of one or more of silica aerogel, polyimide aerogel, cellulose aerogel, and chitosan aerogel.
[0011] The antibacterial functional structure is antibacterial particles doped in the aerogel layer. The antibacterial particles are uniformly dispersed in the gel skeleton of the aerogel during the aerogel preparation process. The antibacterial particles are selected from one or more of nano-silver particles, nano-copper particles, nano-zinc oxide particles, nano-titanium dioxide particles, and silver-loaded zeolite. The particle size of the antibacterial particles is 1-100 nm, and the doping amount is 0.1-10 wt% of the total mass of the aerogel.
[0012] The aerogel layer includes a first aerogel layer and a second aerogel layer, with an antibacterial particle layer disposed between the first aerogel layer and the second aerogel layer; the antibacterial particle layer is applied to the surface of the first aerogel layer by atomization spraying, and the second aerogel layer covers the antibacterial particle layer and is bonded to the first aerogel layer by a medical-grade adhesive.
[0013] The aerogel layer thickness in the bending area is 0.02–0.5 mm, and the aerogel layer thickness in the non-bending area is 0.1–2.0 mm.
[0014] Includes the following steps: S1: Provides flexible circuit board substrates; S2: At least one aerogel layer is provided on the surface of the flexible circuit board substrate; S3: An antibacterial functional structure is provided in or between the aerogel layers, wherein the antibacterial particles in the antibacterial functional structure meet the biocompatibility requirements of the ISO10993 series standards. S4: Control the thickness of the aerogel layer in the bending area of the flexible circuit board to be less than the thickness of the aerogel layer in the non-bending area.
[0015] The antibacterial functional structure is fabricated in two ways: (a) Antibacterial particles were added to the aerogel precursor solution, and after dispersion, gelation, aging, solvent replacement and drying, an aerogel layer in which antibacterial particles were uniformly doped into the gel skeleton was obtained. (b) Apply a mask to the surface of the first aerogel layer, and spray antibacterial particles onto the exposed area using an atomizing spraying method. After removing the mask, bond the second aerogel layer to the first aerogel layer with a medical-grade adhesive.
[0016] The atomization spraying process parameters are as follows: the distance between the spray gun and the substrate is 30-150mm, the spray gun moving speed is 500-2000mm / s, the atomization pressure is 0.1-0.6MPa, the spraying environment temperature is 15-40℃, and the relative humidity is 30-70%; the mask is a physical mask, selected from metal masks, plastic masks, or composite masks, and the accuracy of the mask is controlled within ±0.1mm.
[0017] The thickness of the aerogel layer in the bending area is controlled to be 0.02–0.5 mm, and the thickness of the aerogel layer in the non-bending area is controlled to be 0.1–2.0 mm.
[0018] The matrix material of the aerogel layer in step (2) is selected from one or more of silica aerogel, polyimide aerogel, cellulose aerogel, and chitosan aerogel; The antibacterial particles in step (3) are selected from one or more of nano-silver particles, nano-copper particles, nano-zinc oxide particles, nano-titanium dioxide particles, and silver-loaded zeolite, and the particle size of the antibacterial particles is 1 to 100 nm.
[0019] As can be seen from the above, the medical-grade antibacterial flexible circuit board provided by one or more embodiments of this specification has the following beneficial effects: (1) Multifunctional integration: By setting antibacterial function in or between the aerogel layers, the flexible circuit board can simultaneously have the dual functions of heat insulation and antibacterial, without the need to add an additional antibacterial coating, reducing the overall thickness and maintaining the flexibility of the flexible circuit board.
[0020] (2) Strong bonding of antibacterial particles: In technical solution one, antibacterial particles are uniformly mixed into the gel skeleton of aerogel and form an integrated structure with the aerogel matrix. The antibacterial particles are not easy to fall off and the antibacterial performance is long-lasting and stable. In technical solution two, the selective coating of antibacterial particles is achieved by atomized spraying combined with mask blocking process, which not only ensures the antibacterial effect, but also ensures the effective adhesion between aerogel layers.
[0021] (3) High bending reliability: By precisely controlling the thickness of the aerogel in the bending area, this invention ensures that the flexible circuit board will not be affected by the excessive thickness of the aerogel layer during the bending process, and also avoids the thermal insulation effect being affected by the excessive thinness of the aerogel layer.
[0022] (4) Strong process feasibility: Both technical solutions of the present invention adopt mature process methods such as doping method and atomization spraying method. The process parameters are controllable and suitable for industrial production.
[0023] (5) Wide range of applications: This invention can be widely applied in wearable devices, medical devices, aerospace, consumer electronics and other fields, and is especially suitable for scenarios with dual requirements for heat insulation and antibacterial properties. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in one or more embodiments of this specification or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only one or more embodiments of this specification. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0025] Figure 1 This is a schematic diagram of the structure of the doped antibacterial aerogel medical-grade flexible circuit board of the present invention; Figure 2 This is a schematic diagram of the specific structure of the sandwich-type antibacterial aerogel of the present invention; Figure 3 For the present invention Figure 1 Enlarged structural diagram of region A; Figure 4 The curve shows the antibacterial durability test results of the medical-grade flexible circuit board of the present invention in a simulated body fluid immersion experiment. Figure 5 This is a curve showing the retention rate of thermal insulation performance of the medical-grade flexible circuit board of the present invention after different bending cycles.
[0026] In the figure: 1. Flexible circuit board substrate; 2. LED beads; 3. Doped antibacterial aerogel layer; 4. First aerogel layer; 5. Second aerogel layer; 6. Antibacterial particle layer. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments.
[0028] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. In the present invention, all materials that come into contact with or may come into contact with the human body have undergone biocompatibility evaluation and meet the requirements of ISO 10993-1:2018 "Biological evaluation of medical devices – Part 1: Evaluation and testing in a risk management process".
[0029] Example 1: Preparation of silver-doped silica aerogel nanoparticles by sol-gel method for doped antibacterial aerogel layers I. Preparation of Materials and Equipment In this embodiment, the flexible circuit board substrate 1 is made of medical-grade polyimide (PI) film with a thickness of 25μm. Its biocompatibility has been verified by a third-party testing agency to meet the USP Class VI standard, and its cytotoxicity rating is 0 (ISO10993-5). Medical-grade micro LED beads 2 (wavelength 450nm, used for phototherapy or imaging assistance) and their driving circuit are pre-set on the substrate 1.
[0030] II. Preparation of Nano-Silver Doped Antibacterial Aerogel (1) Preparation of precursor solution: Using tetraethyl orthosilicate (TEOS, medical grade, purity ≥99.9%) as silicon source, TEOS, anhydrous ethanol (medical grade) and purified water were added sequentially to a clean reaction vessel in a molar ratio of 1:4:4. The mixture was stirred at 300 rpm for 10 minutes at room temperature using a magnetic stirrer to ensure thorough mixing. Then, 0.1 mol / L hydrochloric acid solution was slowly added dropwise to adjust the pH to 2.5. The hydrolysis reaction was continued at room temperature for 2 hours to obtain a uniform and transparent silica sol precursor.
[0031] (2) Dispersion and doping of silver nanoparticles: Weigh silver nanoparticles with an average particle size of 30±5nm (modified with polyethylene glycol to improve their dispersibility in the sol), and add them at 2.0wt% of the theoretical total mass of the aerogel. Add the silver nanoparticles to the above sol precursor and use a probe-type ultrasonic disperser (power 200W, frequency 20kHz) to perform ultrasonic dispersion for 20 minutes (interval of 2 minutes after every 5 minutes of ultrasonication to prevent overheating) so that the silver nanoparticles are uniformly dispersed in the sol without obvious agglomeration. After dispersion, let it stand in a dark room for 30 minutes to eliminate bubbles.
[0032] (3) Gelation and aging: Under stirring, 1.0 mol / L ammonia solution was added dropwise to the above sol containing nano-silver to adjust the pH to 7.5. After stirring for 3 minutes, the sol was poured into a pre-made mold (the mold size corresponds to the area on the flexible circuit board surface where aerogel needs to be set). The mold was allowed to stand at room temperature (25±2℃) for gelation. Gelation was completed in about 20 minutes, forming a wet gel doped with nano-silver. The wet gel was sealed and aged at room temperature for 24 hours to further improve the cross-linking of the gel network structure.
[0033] (4) Solvent replacement: After aging, the wet gel is immersed in anhydrous ethanol for solvent replacement. Fresh anhydrous ethanol is replaced every 6 hours for a total of 4 replacements to fully remove moisture and unreacted raw materials from the wet gel.
[0034] (5) Drying: Supercritical carbon dioxide drying was used. The wet gel after solvent replacement was placed in a supercritical drying vessel, and supercritical drying was carried out at a temperature of 40℃ and a pressure of 10MPa using high-purity carbon dioxide as the medium. After maintaining this temperature for 4 hours, the pressure was slowly released to atmospheric pressure to obtain nano-silver doped silica aerogel. The density of the aerogel was measured to be 0.12 g / cm³. 3 It has a porosity of 92%, an average pore size of 25 nm, and a thermal conductivity of 0.018 W / (m·K).
[0035] III. Integration of Silver-Doped Aerogels on Flexible Circuit Boards (1) The nano-silver doped aerogel prepared above is bonded to the surface of the flexible circuit board substrate 1 using medical-grade silicone pressure-sensitive adhesive. The bonding operation is carried out in a clean room with an ISO Class 7 cleanliness level. The bonding pressure is controlled at 0.2 to 0.5 MPa and the bonding temperature is controlled at 40 to 50°C to ensure the bonding strength between the aerogel and the substrate 1.
[0036] (2) The aerogel layer 3 covers the area around the LED bead 2 and has an opening reserved directly above the LED bead 2 to allow light to pass through. The aerogel layer 3 serves as a heat insulation layer to block the heat generated by the LED bead 2 from being conducted to the back of the substrate 1 (i.e., the side 14 in contact with human skin).
[0037] (3) Thickness control in the bending area: In the preset bending area, the thickness of the aerogel layer 3 is precisely controlled to 0.08±0.02mm by a precisely controlled scraper coating process before bonding; in the non-bending area, the thickness of the aerogel layer 3 is controlled to 0.50±0.05mm. The thickness difference is achieved by setting grooves of different depths in the mold.
[0038] IV. Performance Testing and Evaluation (1) Antibacterial performance test: Referring to ISO22196:2011 "Determination of antibacterial activity of plastics and other non-porous materials", the antibacterial rate of the sample against Staphylococcus aureus (ATCC6538) and Escherichia coli (ATCC8739) was tested by the film method. The test results showed that after 24 hours of treatment, the antibacterial rate of the sample against Staphylococcus aureus was 99.7% and the antibacterial rate against Escherichia coli was 99.5%. After soaking the sample in simulated body fluid (SBF, pH7.4, ionic composition simulated human blood plasma) for 7 days, the antibacterial rate was tested again, and the results were 99.4% and 99.1%, respectively. This shows that the nano-silver particles are firmly bonded to the aerogel skeleton and the antibacterial performance is long-lasting.
[0039] (2) Biocompatibility test: The cytotoxicity test (L929 mouse fibroblasts, MTT method) was conducted according to ISO10993-5:2009 standard. The results showed that the relative cell growth rate (RGR) was 92% and the cytotoxicity rating was 1 (the qualified standard is ≤2). The skin sensitization test was conducted according to ISO10993-10:2010 standard. The result was no sensitization. The irritation test was conducted according to ISO10993-23:2021 standard. The result was no irritation.
[0040] (3) Thermal insulation performance test: After the LED beads 2 operated continuously at maximum power (100mW) for 30 minutes, the surface temperature of the back side (skin contact side 14) of the substrate 1 was measured using an infrared thermal imager. The results showed that the back side temperature of the sample with the doped antibacterial aerogel layer 3 was 38.2℃; the back side temperature of the control sample without the aerogel layer was 46.5℃. The above results indicate that the aerogel layer 3 of the present invention can reduce the surface temperature by 8.3℃, making it lower than the medical safety limit (41℃).
[0041] (4) Bending reliability test: Repeated bending test was carried out in accordance with the IPC-TM-6502.4.3 standard. The bending angle was 180°, the inner radius of bending was 1.5 mm, and the bending frequency was 1 Hz. The results showed that after 15,000 bending cycles, the aerogel layer 3 in the bending area had no cracks or delamination, and the interface between the aerogel layer 3 and the substrate 1 was intact. After 20,000 bending cycles, there were still no visible defects. However, the control sample, which did not have differential control of the bending area thickness, showed cracks in the aerogel layer after about 4,000 bending cycles and delamination after 8,000 bending cycles.
[0042] (5) Scanning electron microscopy observation: The microstructure of the aerogel was observed by field emission scanning electron microscopy (FE-SEM). The results showed that the nano-silver particles (bright spots) were uniformly dispersed in the three-dimensional porous network framework of the aerogel, with the particle size distribution concentrated in 20-50 nm and no obvious agglomeration.
[0043] Example 2: Silver-loaded zeolite sandwich structure prepared by atomized spraying method I. Preparation of the first aerogel layer 4 Pure silica aerogel was prepared according to the method in step two of Example 1 (but without adding silver nanoparticles) as the first aerogel layer 4. The thickness of this layer was controlled at 0.30±0.05mm, serving as the main heat insulation layer and biological isolation layer.
[0044] II. Preparation of the second aerogel layer 5 The second aerogel layer 5 was prepared using the same method, with a thickness controlled at 0.20±0.05 mm. This layer is mainly used for mechanical protection and to provide an adhesive interface with the first aerogel layer 4. The surface of the second aerogel layer 5 was treated with plasma (Ar / O2 mixed atmosphere, power 100W, treatment time 60 seconds) to improve its surface energy and enhance its bonding strength with the adhesive.
[0045] III. Preparation of Silver-loaded Zeolite Antibacterial Spray Solution (1) Preparation of silver-loaded zeolite: Using type 4A zeolite molecular sieve as a carrier, silver ions (Ag) were transferred to silver-loaded zeolite via ion exchange. + The silver-loaded zeolite was loaded onto the pores and surface of the zeolite. The specific operation was as follows: 10g of 4A zeolite was dispersed in 100mL of 0.1mol / L silver nitrate solution, stirred and exchanged at 60℃ for 6 hours, filtered, and washed with purified water until no nitrate ions were detected (tested with sodium chloride solution). It was then dried at 80℃ for 12 hours to obtain silver-loaded zeolite (silver content of about 12wt%). The silver-loaded zeolite was then ground into particles with an average particle size of 1-2μm.
[0046] (2) Preparation of antibacterial spray: The above silver-loaded zeolite particles were dispersed in a mixed solvent of medical grade anhydrous ethanol and purified water (volume ratio 7:3) at a solid content of 2.5 wt%. 0.5 wt% polyvinylpyrrolidone (PVP, K30 grade) was added as a dispersant and film-forming aid. The mixture was dispersed for 15 minutes using a high-shear emulsifier (speed 10000 rpm) and then treated with an ultrasonic water bath for 10 minutes to eliminate bubbles, resulting in a uniform and stable antibacterial spray. The spray showed no significant sedimentation after standing at room temperature for 24 hours.
[0047] IV. Atomized Spraying Process (1) such as Figure 3 As shown, the first aerogel layer 4 is laid flat on a clean workbench, and a precision-etched stainless steel mask (0.1 mm thick, opening accuracy ±0.05 mm) is placed over its surface. The mask covers the area to be bonded to the second aerogel layer 5 (the bonding area, with a 2 mm wide perimeter border), exposing the central area (10 mm × 15 mm) where antibacterial particles need to be coated.
[0048] (2) High-precision atomizing spray gun (nozzle diameter 0.3mm) is used for spraying in a spraying room with a cleanliness level of ISO Class 6 (temperature 25±2℃, relative humidity 50±5%).
[0049] The spraying parameters are as follows: distance between spray gun and substrate 80±5mm, spray gun moving speed 1200±50mm / s, atomization pressure 0.25±0.02MPa, spraying path is a reciprocating serpentine path, and overlap rate is approximately 30%. Based on the target coating amount (approximately 5μg / cm³), 2 (Silver equivalent), sprayed in 3 coats, with an interval of about 30 seconds between each coat, to avoid the coating becoming too wet and causing unevenness.
[0050] (3) After the spraying is completed, the first aerogel layer 4, together with the mask, is moved into the circulating hot air oven and dried at 60±2℃ for 2 hours to allow the solvent in the spray liquid to evaporate completely, and the silver-loaded zeolite particles are firmly attached to the aerogel surface to form an antibacterial particle layer 6.
[0051] (4) After drying, carefully remove the mask to expose the clean area to be pasted. Use an optical microscope to check the clarity of the boundaries of the antibacterial particle layer 6 to ensure that the particles have not penetrated into the area to be pasted.
[0052] V. Bonding of the first aerogel layer and the second aerogel layer A medical-grade two-component polyurethane adhesive (compliant with ISO 10993-5 cytotoxicity requirements) was used to uniformly apply the adhesive to the bonding area using screen printing, with the adhesive layer thickness controlled at 20±5μm. Then, a second aerogel layer 5 was placed on top of the antibacterial particle layer 6 and cured at room temperature for 24 hours under a pressure of 0.3MPa, allowing the two aerogel layers to bond firmly together through the adhesive.
[0053] VI. Integration on Flexible Circuit Board Substrates The prepared sandwich-type aerogel composite structure (first aerogel layer 4 + antibacterial particle layer 6 + second aerogel layer 5) is bonded to the surface of the flexible circuit board substrate 1 using medical-grade acrylic pressure-sensitive adhesive, covering the area around the LED beads 2. The total aerogel thickness in the bending area is controlled at 0.12±0.03mm, and the total thickness in the non-bending area is controlled at 0.50±0.05mm.
[0054] VII. Performance Testing and Evaluation (1) Antibacterial performance test: The sample was tested according to the method in Example 1. The antibacterial rate against Staphylococcus aureus was 99.3% and the antibacterial rate against Escherichia coli was 99.0%. Since the antibacterial particles are sandwiched between two layers of aerogel and are not directly exposed to the surface, the risk of antibacterial particles falling into the human body is avoided, which further improves biosafety.
[0055] (2) Interlayer bonding strength test: The 180° peel strength test was conducted in accordance with the ASTM D3330 standard. The results showed that the peel strength of the area to be bonded was 8.5±0.5N / cm, which is much higher than the bonding strength requirement of ordinary tape (usually ≥4N / cm). This indicates that the blocking process of the mask effectively ensured the cleanliness of the bonding area 12 and ensured reliable interlayer bonding.
[0056] (3) Thermal resistance test: The equivalent thermal conductivity of the composite structure was tested using a thermal conductivity meter with heat flow method. The results showed that its equivalent thermal conductivity at room temperature was 0.021 W / (m·K), which was basically equivalent to the thermal conductivity of a single layer of aerogel. This indicates that the intermediate antibacterial particle layer 6 did not have a noticeable deterioration effect on the thermal insulation performance.
[0057] (4) Scanning electron microscopy and energy dispersive spectroscopy analysis: The cross-section of the sandwich structure was analyzed by SEM-EDS. It can be seen that there is an antibacterial particle layer 6 (antibacterial particle enrichment layer) with a thickness of about 5-10 μm between the first aerogel layer 4 and the second aerogel layer 5. Energy dispersive spectroscopy analysis showed that the silver element signal was significantly enriched in this layer, while no silver element was detected in the area to be pasted, which confirmed that the mask played an effective blocking role.
[0058] Example 3 (Alternative material to technical solution 1: chitosan-based antibacterial aerogel) I. Preparation of Chitosan / Silver Nanoparticle Composite Aerogel This embodiment aims to utilize the biocompatibility and intrinsic antibacterial activity of chitosan itself, in synergy with nano-silver, to achieve a more efficient antibacterial effect.
[0059] (1) Dissolve 2.0 g of chitosan (degree of deacetylation ≥90%, medical grade, molecular weight approximately 500,000 Da) in 100 mL of 2% acetic acid aqueous solution and stir at room temperature for 12 hours until completely dissolved to obtain a clear chitosan solution. Filter the solution through a 0.45 μm filter membrane to remove insoluble matter.
[0060] (2) Add nano silver particles (particle size 20 nm, silver content 1.5 wt% of dry weight of aerogel) and 0.5 wt% glutaraldehyde (as crosslinking agent) to the above chitosan solution, stir and disperse evenly, and then sonicate for 15 minutes.
[0061] (3) The mixture was injected into the mold and frozen at -20°C for 12 hours. Then it was transferred to a freeze dryer and freeze-dried at -50°C and 10Pa vacuum for 48 hours to obtain chitosan / silver nanocomposite aerogel.
[0062] (4) The composite aerogel was vacuum crosslinked at 120°C for 2 hours to improve its structural stability in the water environment.
[0063] II. Performance Testing (1) The chitosan / silver nanocomposite aerogel prepared in this embodiment has a sponge-like three-dimensional network structure with a density of 0.08 g / cm³. 3 It has a porosity of 95%. Its antibacterial rate against Staphylococcus aureus is 99.9%, and against Escherichia coli is 99.6%. Due to the antibacterial activity of chitosan itself, it exhibits a synergistic effect with nano-silver, resulting in a superior antibacterial effect compared to pure silica-based doped systems.
[0064] (2) The cytotoxicity test (ISO10993-5) showed that the relative cell proliferation rate was 95% and the cytotoxicity rating was 0 (non-toxic), which is better than the silica-based system and more suitable for medical applications that come into direct contact with human skin or wounds.
[0065] (3) The aerogel prepared in this embodiment has a hydrophilic surface (water contact angle of about 45°), which provides better comfort and fit in wearable sweat monitoring and other scenarios. At the same time, its flexibility is better than that of silica aerogel, and the thickness control in the bending area is easier.
[0066] Example 4 (Optimization and selection of atomization spraying process parameters) This embodiment systematically examines the effects of different atomization spraying parameters on the uniformity of antibacterial particle coating, coating accuracy, and interlayer adhesion strength in order to determine the optimal process window.
[0067] 1. Experimental Design Using silver-loaded zeolite as antibacterial particles, the antibacterial spray coating solution was prepared according to the formulation of Example 2. A three-factor three-level orthogonal experimental design (L9 orthogonal array) was adopted to investigate the effects of three factors, namely the distance between the spray gun and the substrate (A), the moving speed of the spray gun (B), and the atomization pressure (C), on the distribution uniformity of antibacterial particles and the cleanliness of the area to be bonded. The level settings of each factor are as follows:
[0068] 2. Evaluation Methods Distribution uniformity of antibacterial particles: 9 test points (3×3 grid) are randomly selected in the spray coating area, and the signal intensity of silver element at each point is measured by the energy dispersive spectrometer (SEM-EDS) attached to the scanning electron microscope to calculate the relative standard deviation (RSD). RSD≤15% is rated as "excellent", 15%<RSD≤25% is rated as "good", and RSD>25% is rated as "poor".
[0069] Cleanliness of the area to be bonded: X-ray photoelectron spectroscopy (XPS) is used to detect the residual amount of silver element in the area to be bonded, which is expressed as atomic percentage. ≤0.1% is rated as "excellent", 0.1%<≤0.3% is rated as "good", and >0.3% is rated as "poor".
[0070] Interlayer bonding strength: The 180° peel strength test is carried out with reference to ASTM D3330.
[0071] 3. Experimental Results
[0072] 4. Preferred Process Conditions Based on the above results, the optimal process condition is the parameter combination of Experiment No. 5: the distance between the spray gun and the substrate is 80mm, the moving speed of the spray gun is 1200mm / s, and the atomization pressure is 0.25MPa. Under these conditions, the antibacterial particles are uniformly distributed (RSD=9.6%), the area to be bonded is highly clean (silver residual amount <0.05%), and the interlayer bonding strength is the highest (8.6N / cm). This condition serves as the core benchmark for the preferred parameter range of the atomization spraying process of the present invention.
[0073] Example 5 (Accelerated Life Test on the Effect of Thickness Control in Bending Area on Long-term Reliability) This example systematically verifies the effect of the thickness of the aerogel layer in the bending area on the long-term reliability of the medical-grade flexible printed circuit board under simulated use conditions.
[0074] 1. Sample Preparation Using the doped antibacterial aerogel system of Example 1, four samples (A, B, C, and D) with different aerogel thicknesses in the bending regions were prepared, while the thickness in the non-bending regions was uniformly 0.5 mm.
[0075] II. Accelerated Life Test Conditions Referring to the reliability testing standards for medical devices, the following accelerated aging conditions were set: temperature 70℃ (acceleration factor approximately 2.5, relative to room temperature 25℃), relative humidity 85%RH, and dynamic bending cycle was applied simultaneously (bending angle 180°, bending radius 2mm, frequency 0.5Hz). The test endpoint indicators were: (1) visible cracks appeared in the aerogel layer; (2) the delamination area between the aerogel layer and substrate 1 was ≥ 5% of the total area; (3) the change rate of thermal insulation performance (thermal conductivity) was ≥ 20%.
[0076] III. Test Results
[0077] The equivalent service life is calculated using an acceleration factor of 2.5, based on 10 hours of use per day and 100 bends per hour.
[0078] IV. Conclusion The above results demonstrate that controlling the thickness of the aerogel layer in the bending region has a decisive impact on the long-term reliability of medical-grade flexible circuit boards. When the thickness ratio of the bending region to the non-bending region is controlled below 0.2 (samples A and B), the devices can withstand more than 50,000 bending cycles under accelerated aging conditions without performance degradation, with an equivalent service life exceeding 5 years, meeting the service life requirements (typically ≥3 years) of most wearable medical devices and implantable devices. However, sample D, which did not undergo thickness differentiation control, has a service life of less than 1 year, failing to meet the basic requirements for medical-grade applications.
[0079] Example 6 (Verification of comprehensive performance in a simulated bodily fluid environment for medical applications) This embodiment simulates the complex environment of wearable medical devices coming into contact with sweat, sebum, and repeated friction in actual use, and performs comprehensive performance verification on the medical-grade antibacterial flexible circuit board of the present invention.
[0080] I. Test Conditions The sample prepared in Example 1 was immersed in artificial sweat (composition: sodium chloride 20 g / L, ammonium chloride 17.5 g / L, lactic acid 15 g / L, acetic acid 5 g / L, pH 4.7, according to ISO 3160-2 standard) and immersed for 168 hours (7 days) in a constant temperature shaking incubator at 37°C and 100 rpm. Fresh artificial sweat was replaced every 24 hours. After immersion, the sample was removed, gently rinsed with purified water, and dried at room temperature for 24 hours.
[0081] II. Test Results (1) Appearance inspection: The sample showed no obvious discoloration, swelling, cracks or delamination, and the aerogel layer 3 structure was intact.
[0082] (2) Antibacterial performance retention rate: The antibacterial rates of the samples after soaking were 99.2% for Staphylococcus aureus and 98.8% for Escherichia coli, respectively. Compared with before soaking (99.7% and 99.5%), the retention rates were both over 99%.
[0083] (3) Silver ion release: The concentration of silver ions in the immersion solution was detected by inductively coupled plasma mass spectrometry (ICP-MS). The cumulative release was approximately 0.18 μg / cm², which is far below the safety limit for silver ion release in medical devices (usually <1 μg / cm²). 2 This indicates that the nano-silver is very firmly fixed in the aerogel framework and has high safety in use.
[0084] (4) Thermal insulation performance retention rate: The thermal conductivity after immersion is 0.019 W / (m·K), which is 5.6% of the initial value (0.018 W / (m·K)), which is within the acceptable range.
[0085] (5) Biocompatibility re-evaluation: The cytotoxicity test (ISO10993-5) was performed again on the soaked sample. The relative cell proliferation rate was 91%, and the cytotoxicity rating was still Grade 1, indicating that the sample still maintained good biocompatibility after being soaked in simulated body fluid.
[0086] III. Comprehensive Evaluation The results of this embodiment fully verify the reliability and safety of the medical-grade antibacterial flexible circuit board provided by the present invention in actual medical application scenarios (contact with sweat and body fluids). Under the harsh conditions of simulating 7 days of continuous use, the antibacterial performance, thermal insulation performance, and biocompatibility of the sample all remain at a high level, meeting the actual use requirements of medical-grade devices.
[0087] The present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. In the present invention, all materials that come into contact with or may come into contact with the human body have undergone biocompatibility evaluation and meet the requirements of ISO 10993-1:2018 "Biological evaluation of medical devices – Part 1: Evaluation and testing in a risk management process".
[0088] Example 1: Preparation of silver-doped silica aerogel nanoparticles by sol-gel method for doped antibacterial aerogel layers I. Preparation of Materials and Equipment In this embodiment, the flexible circuit board substrate 1 is made of medical-grade polyimide (PI) film with a thickness of 25μm. Its biocompatibility has been verified by a third-party testing agency to meet the USP Class VI standard, and its cytotoxicity rating is 0 (ISO10993-5). Medical-grade micro LED beads 2 (wavelength 450nm, used for phototherapy or imaging assistance) and their driving circuit are pre-set on the substrate 1.
[0089] II. Preparation of Nano-Silver Doped Antibacterial Aerogel (1) Preparation of precursor solution: Using tetraethyl orthosilicate (TEOS, medical grade, purity ≥99.9%) as silicon source, TEOS, anhydrous ethanol (medical grade) and purified water were added sequentially to a clean reaction vessel in a molar ratio of 1:4:4. The mixture was stirred at 300 rpm for 10 minutes at room temperature using a magnetic stirrer to ensure thorough mixing. Then, 0.1 mol / L hydrochloric acid solution was slowly added dropwise to adjust the pH to 2.5. The hydrolysis reaction was continued at room temperature for 2 hours to obtain a uniform and transparent silica sol precursor.
[0090] (2) Dispersion and doping of silver nanoparticles: Silver nanoparticles with an average particle size of 30±5nm (modified with polyethylene glycol to improve their dispersibility in the sol) were weighed and added at an amount of 2.0wt% of the theoretical total mass of the aerogel. The silver nanoparticles were added to the above sol precursor and ultrasonically dispersed for 20 minutes using a probe-type ultrasonic disperser (power 200W, frequency 20kHz) (with a 2-minute interval between every 5 minutes of ultrasonication to prevent overheating) to ensure uniform dispersion of the silver nanoparticles in the sol without obvious agglomeration. After dispersion, the mixture was allowed to stand in a dark room for 30 minutes to eliminate air bubbles.
[0091] (3) Gelation and aging: Under stirring, 1.0 mol / L ammonia solution was added dropwise to the above sol containing nano-silver to adjust the pH to 7.5. After stirring for 3 minutes, the sol was poured into a pre-made mold (the mold size corresponds to the area on the flexible circuit board surface where aerogel needs to be set). The mold was allowed to stand at room temperature (25±2℃) for gelation. Gelation was completed in about 20 minutes, forming a wet gel doped with nano-silver. The wet gel was sealed and aged at room temperature for 24 hours to further improve the cross-linking of the gel network structure.
[0092] (4) Solvent replacement: After aging, the wet gel is immersed in anhydrous ethanol for solvent replacement. Fresh anhydrous ethanol is replaced every 6 hours for a total of 4 replacements to fully remove moisture and unreacted raw materials from the wet gel.
[0093] (5) Drying: Supercritical carbon dioxide drying was used. The wet gel after solvent replacement was placed in a supercritical drying vessel, and supercritical drying was carried out at a temperature of 40℃ and a pressure of 10MPa using high-purity carbon dioxide as the medium. After maintaining this temperature for 4 hours, the pressure was slowly released to atmospheric pressure to obtain nano-silver doped silica aerogel. The density of the aerogel was measured to be 0.12 g / cm³. 3 It has a porosity of 92%, an average pore size of 25 nm, and a thermal conductivity of 0.018 W / (m·K).
[0094] III. Integration of Silver-Doped Aerogels on Flexible Circuit Boards (1) The nano-silver doped aerogel prepared above was bonded to the surface of the flexible circuit board substrate 1 using medical-grade silicone pressure-sensitive adhesive. The bonding operation was carried out in a clean room with an ISO Class 7 cleanliness level. The bonding pressure was controlled at 0.2 to 0.5 MPa and the bonding temperature was controlled at 40 to 50°C to ensure the bonding strength between the aerogel and the substrate 1.
[0095] (2) The aerogel layer 3 covers the area around the LED bead 2 and has an opening reserved directly above the LED bead 2 to allow light to pass through. The aerogel layer 3 serves as a heat insulation layer to block the heat generated by the LED bead 2 from being conducted to the back of the substrate 1 (i.e., the side 14 in contact with human skin).
[0096] (3) Thickness control in the bending area: In the preset bending area, the thickness of the aerogel layer 3 is precisely controlled to 0.08±0.02mm by a precisely controlled scraper coating process before bonding; in the non-bending area, the thickness of the aerogel layer 3 is controlled to 0.50±0.05mm. The thickness difference is achieved by setting grooves of different depths in the mold.
[0097] Performance Testing and Evaluation (1) Antibacterial performance test: Referring to ISO22196:2011 "Determination of antibacterial activity of plastics and other non-porous materials", the antibacterial rate of the sample against Staphylococcus aureus (ATCC6538) and Escherichia coli (ATCC8739) was tested by the film method. The test results showed that after 24 hours of treatment, the antibacterial rate of the sample against Staphylococcus aureus was 99.7% and the antibacterial rate against Escherichia coli was 99.5%. After soaking the sample in simulated body fluid (SBF, pH7.4, ionic composition simulated human blood plasma) for 7 days, the antibacterial rate was tested again, and the results were 99.4% and 99.1%, respectively. This shows that the nano-silver particles are firmly bonded to the aerogel skeleton and the antibacterial performance is long-lasting.
[0098] (2) Biocompatibility test: The cytotoxicity test (L929 mouse fibroblasts, MTT method) was conducted according to ISO10993-5:2009 standard. The results showed that the relative cell growth rate (RGR) was 92% and the cytotoxicity rating was 1 (the qualified standard is ≤2). The skin sensitization test was conducted according to ISO10993-10:2010 standard. The result was no sensitization. The irritation test was conducted according to ISO10993-23:2021 standard. The result was no irritation.
[0099] (3) Thermal insulation performance test: After the LED lamp bead 2 worked continuously at the maximum power (100mW) for 30 minutes, the surface temperature of the back side (human skin contact side 14) of the substrate 1 was measured by infrared thermal imager. The results showed that the back temperature of the sample with the doped antibacterial aerogel layer 3 was 38.2℃; the back temperature of the control sample without the aerogel layer was 46.5℃. The above results show that the aerogel layer 3 of the present invention can reduce the surface temperature by 8.3℃, making it lower than the medical safety limit (41℃).
[0100] (4) Bending reliability test: Repeated bending test was carried out in accordance with the IPC-TM-6502.4.3 standard. The bending angle was 180°, the inner radius of bending was 1.5 mm, and the bending frequency was 1 Hz. The results showed that after 15,000 bending cycles, the aerogel layer 3 in the bending area had no cracks or delamination, and the interface between the aerogel layer 3 and the substrate 1 was intact. After 20,000 bending cycles, there were still no visible defects. However, the control sample, which did not have differential control of the bending area thickness, showed cracks in the aerogel layer after about 4,000 bending cycles and delamination after 8,000 bending cycles.
[0101] (5) Scanning electron microscopy observation: The microstructure of the aerogel was observed by field emission scanning electron microscopy (FE-SEM). The results showed that the nano-silver particles (bright spots) were uniformly dispersed in the three-dimensional porous network framework of the aerogel, with the particle size distribution concentrated in 20-50 nm and no obvious agglomeration.
[0102] Example 2: Silver-loaded zeolite sandwich structure prepared by atomized spraying method I. Preparation of the first aerogel layer 4 Pure silica aerogel was prepared according to the method in step two of Example 1 (but without adding silver nanoparticles) as the first aerogel layer 4; the thickness of this layer was controlled at 0.30±0.05mm, serving as the main heat insulation layer and biological isolation layer.
[0103] II. Preparation of the second aerogel layer 5 The second aerogel layer 5 was prepared using the same method, with a thickness controlled at 0.20±0.05 mm. This layer mainly serves for mechanical protection and provides an interface for bonding with the first aerogel layer 4. The surface of the second aerogel layer 5 was subjected to plasma treatment (Ar / O2 mixed atmosphere, power 100W, treatment time 60 seconds) to increase its surface energy and enhance its bonding strength with the adhesive.
[0104] III. Preparation of Silver-loaded Zeolite Antibacterial Spray Solution (1) Preparation of silver-loaded zeolite: Using type 4A zeolite molecular sieve as a carrier, silver ions (Ag) were transferred to silver-loaded zeolite via ion exchange. + It is loaded on the pores and surface of the zeolite.
[0105] The specific procedure is as follows: 10g of 4A zeolite is dispersed in 100mL of 0.1mol / L silver nitrate solution, stirred and exchanged at 60℃ for 6 hours, filtered, and washed with purified water until no nitrate ions are detected (tested with sodium chloride solution). It is then dried at 80℃ for 12 hours to obtain silver-loaded zeolite (silver content approximately 12wt%). The silver-loaded zeolite is then ground into particles with an average particle size of 1–2μm.
[0106] (2) Preparation of antibacterial spray: The above silver-loaded zeolite particles were dispersed in a mixed solvent of medical grade anhydrous ethanol and purified water (volume ratio 7:3) at a solid content of 2.5 wt%. 0.5 wt% polyvinylpyrrolidone (PVP, K30 grade) was added as a dispersant and film-forming aid. The mixture was dispersed for 15 minutes using a high-shear emulsifier (speed 10000 rpm) and then treated with an ultrasonic water bath for 10 minutes to eliminate bubbles, resulting in a uniform and stable antibacterial spray. The spray showed no significant sedimentation after standing at room temperature for 24 hours.
[0107] IV. Atomized Spraying Process (1) such as Figure 3 As shown, the first aerogel layer 4 is laid flat on a clean workbench, and a stainless steel mask (thickness 0.1mm, opening accuracy ±0.05mm) with precision etching is covered on its surface. The mask covers the area to be bonded to the second aerogel layer 5 (the area to be bonded, with a perimeter border of 2mm width), exposing the central area (area of 10mm×15mm) to be coated with antibacterial particles.
[0108] (2) A high-precision atomizing spray gun (nozzle diameter 0.3 mm) was used for spraying in a spraying chamber with an ISO Class 6 cleanliness level (temperature 25±2℃, relative humidity 50±5%). The spraying parameters were as follows: distance between the spray gun and the substrate 80±5 mm, spray gun moving speed 1200±50 mm / s, atomization pressure 0.25±0.02 MPa, and a reciprocating serpentine spraying path with an overlap rate of approximately 30%. The coating amount was determined based on the target coating weight (approximately 5 μg / cm³). 2(Silver equivalent), sprayed in 3 coats, with an interval of about 30 seconds between each coat, to avoid the coating becoming too wet and causing unevenness.
[0109] (3) After the spraying is completed, the first aerogel layer 4, together with the mask, is moved into the circulating hot air oven and dried at 60±2℃ for 2 hours to allow the solvent in the spray liquid to evaporate completely, and the silver-loaded zeolite particles are firmly attached to the aerogel surface to form an antibacterial particle layer 6.
[0110] (4) After drying, carefully remove the mask to expose the clean area to be pasted. Use an optical microscope to check the clarity of the boundary of the antibacterial particle layer 6 to ensure that the particles have not penetrated into the area to be pasted.
[0111] V. Bonding of the first aerogel layer and the second aerogel layer Medical-grade two-component polyurethane adhesive (compliant with ISO10993-5 cytotoxicity requirements) is used in the area to be pasted. The adhesive is evenly applied to the pasting area using screen printing, with the thickness of the adhesive layer controlled at 20±5μm. Then, the second aerogel layer 5 is placed on top of the antibacterial particle layer 6 and cured at room temperature for 24 hours under a pressure of 0.3MPa, so that the two aerogel layers are firmly bonded together by the adhesive.
[0112] VI. Integration on Flexible Circuit Board Substrates The prepared sandwich-type aerogel composite structure (first aerogel layer 4, antibacterial particle layer 6, and second aerogel layer 5) is bonded to the surface of the flexible circuit board substrate 1 using medical-grade acrylic pressure-sensitive adhesive, covering the area around the LED beads 2. The total aerogel thickness in the bending area is controlled at 0.12±0.03mm, and the total thickness in the non-bending area is controlled at 0.50±0.05mm.
[0113] VII. Performance Testing and Evaluation (1) Antibacterial performance test: The sample was tested according to the method in Example 1. The antibacterial rate against Staphylococcus aureus was 99.3% and the antibacterial rate against Escherichia coli was 99.0%. Since the antibacterial particles were sandwiched between two layers of aerogel and were not directly exposed to the surface, the risk of the antibacterial particles falling off and entering the human body was avoided, which further improved the biosafety.
[0114] (2) Interlayer bonding strength test: The 180° peel strength test was conducted in accordance with the ASTM D3330 standard. The results showed that the peel strength of the area to be bonded was 8.5±0.5N / cm, which is much higher than the bonding strength requirement of ordinary tape (usually ≥4N / cm). This indicates that the blocking process of the mask effectively ensured the cleanliness of the bonding area 12 and ensured reliable interlayer bonding.
[0115] (3) Thermal resistance test: The equivalent thermal conductivity of the composite structure was tested using a thermal conductivity meter with heat flow method. The results showed that its equivalent thermal conductivity at room temperature was 0.021 W / (m·K), which was basically equivalent to the thermal conductivity of a single layer of aerogel. This indicates that the intermediate antibacterial particle layer 6 did not have a noticeable deterioration effect on the thermal insulation performance.
[0116] (4) Scanning electron microscopy and energy dispersive spectroscopy analysis: The cross-section of the sandwich structure was analyzed by SEM-EDS. It can be seen that there is an antibacterial particle layer 6 (antibacterial particle enrichment layer) with a thickness of about 5-10 μm between the first aerogel layer 4 and the second aerogel layer 5. Energy dispersive spectroscopy analysis showed that the silver element signal was significantly enriched in this layer, while no silver element was detected in the area to be pasted, which confirmed that the mask played an effective blocking role.
[0117] Example 3 Alternative material to Example 1: Chitosan-based antibacterial aerogel I. Preparation of Chitosan or Silver Nanocomposite Aerogels This embodiment aims to utilize the biocompatibility and intrinsic antibacterial activity of chitosan itself, in synergy with nano-silver, to achieve a more efficient antibacterial effect.
[0118] (1) Dissolve 2.0 g of chitosan (degree of deacetylation ≥90%, medical grade, molecular weight approximately 500,000 Da) in 100 mL of 2% acetic acid aqueous solution and stir at room temperature for 12 hours until completely dissolved to obtain a clear chitosan solution. Filter the solution through a 0.45 μm filter membrane to remove insoluble matter.
[0119] (2) Add nano silver particles (particle size 20 nm, silver content 1.5 wt% of dry weight of aerogel) and 0.5 wt% glutaraldehyde (as crosslinking agent) to the above chitosan solution, stir and disperse evenly, and then sonicate for 15 minutes.
[0120] (3) The mixture was injected into the mold and frozen at -20°C for 12 hours. Then it was transferred to a freeze dryer and freeze-dried at -50°C and 10Pa vacuum for 48 hours to obtain chitosan / silver nanocomposite aerogel.
[0121] (4) The composite aerogel was vacuum crosslinked at 120°C for 2 hours to improve its structural stability in the water environment.
[0122] II. Performance Testing (1) The chitosan / silver nanocomposite aerogel prepared in this embodiment has a sponge-like three-dimensional network structure with a density of 0.08 g / cm³. 3, with a porosity of 95%. Its antibacterial rate against Staphylococcus aureus is 99.9%, and the antibacterial rate against Escherichia coli is 99.6%. Since chitosan itself has antibacterial activity, it produces a synergistic effect with nano-silver, and the antibacterial effect is better than that of a pure silica-based doping system.
[0123] (2) Cytotoxicity test (ISO10993-5) shows that the relative cell proliferation rate is 95%, and the cytotoxicity grade is 0 (non-toxic), which is superior to the silica-based system and more suitable for medical application scenarios involving direct contact with human skin or wounds.
[0124] (3) The aerogel prepared in this example has a hydrophilic surface (water contact angle of about 45°), which provides better comfort and conformability in scenarios such as wearable sweat monitoring. Meanwhile, its flexibility is superior to that of silica aerogel, making it easier to control the thickness in the bent area.
[0125] Example 4 Optimization and selection of process parameters for atomized spraying In this example, the effects of different atomized spraying parameters on the coating uniformity, coating precision and interlayer adhesion strength of antibacterial particles are systematically investigated to determine the optimal process window.
[0126] 1. Experimental design Using silver-loaded zeolite as the antibacterial particles, the antibacterial spraying liquid is prepared according to the formula of Example 2. A three-factor three-level orthogonal experimental design (L9 orthogonal array) is adopted to investigate the effects of three factors, namely the distance between the spray gun and the substrate (A), the moving speed of the spray gun (B), and the atomization pressure (C), on the distribution uniformity of antibacterial particles and the cleanliness of the area to be bonded.
[0127] The level settings of each factor are as follows:
[0128] 2. Evaluation methods Distribution uniformity of antibacterial particles: 9 test points (3×3 grid) are randomly selected in the spraying area, the silver element signal intensity at each point is measured by the energy dispersive spectrometer (SEM-EDS) attached to the scanning electron microscope, and the relative standard deviation (RSD) is calculated. RSD ≤ 15% is rated as "excellent", 15% < RSD ≤ 25% is rated as "good", and RSD > 25% is rated as "poor".
[0129] Cleanliness of the area to be bonded: X-ray photoelectron spectroscopy (XPS) is used to detect the residual amount of silver element in the area to be bonded, which is expressed as atomic percentage. ≤ 0.1% is rated as "excellent", 0.1% < ≤ 0.3% is rated as "good", and > 0.3% is rated as "poor".
[0130] Interlayer adhesion strength: The 180° peel strength test is carried out with reference to ASTM D3330.
[0131] III. Experimental Results
[0132] IV. Optimization of Process Conditions Based on the above results, the optimal process conditions are the parameter combination of Experiment No. 5: a distance of 80 mm between the spray gun and the substrate, a spray gun moving speed of 1200 mm / s, and an atomization pressure of 0.25 MPa. Under these conditions, the antibacterial particles are evenly distributed (RSD = 9.6%), the area to be bonded is highly clean (silver residue < 0.05%), and the interlayer bonding strength is the highest (8.6 N / cm). These conditions serve as the core benchmark for the preferred parameter range of the atomization spraying process of this invention.
[0133] Example 5: Impact of bending area thickness control on long-term reliability - Accelerated life testing This embodiment systematically verifies the impact of the aerogel layer thickness in the bending region on the long-term reliability of medical-grade flexible circuit boards under simulated usage conditions.
[0134] I. Sample Preparation Using the doped antibacterial aerogel system of Example 1, four samples (A, B, C, and D) with different aerogel thicknesses in the bending regions were prepared, while the thickness in the non-bending regions was uniformly 0.5 mm.
[0135] II. Accelerated Life Test Conditions Referring to the reliability testing standards for medical devices, the following accelerated aging conditions were set: temperature 70℃ (acceleration factor approximately 2.5, relative to room temperature 25℃), relative humidity 85%RH, and dynamic bending cycles were applied simultaneously (bending angle 180°, bending radius 2mm, frequency 0.5Hz). The test endpoint was: (1) Visible cracks appear in the aerogel layer; (2) The area of the aerogel layer separated from the substrate 1 is ≥ 5% of the total area; (3) The rate of change of thermal insulation performance (thermal conductivity) is ≥20%.
[0136] III. Test Results
[0137] The equivalent service life is calculated using an acceleration factor of 2.5, based on 10 hours of use per day and 100 bends per hour.
[0138] The above results indicate that the thickness control of the aerogel layer in the bending region has a decisive impact on the long-term reliability of medical-grade flexible circuit boards. When the thickness ratio of the bending region to the non-bending region is controlled below 0.2 (samples A and B), the device can withstand more than 50,000 bending cycles under accelerated aging conditions without performance degradation, with an equivalent service life of more than 5 years, meeting the service life requirements of most wearable medical devices and implantable devices (usually ≥3 years). However, sample D, which did not undergo thickness differentiation control, has a service life of less than 1 year and cannot meet the basic requirements for medical-grade applications.
[0139] Example 6: Medical-grade application scenario verification of comprehensive performance in simulated body fluid environment This embodiment simulates the complex environment of wearable medical devices coming into contact with sweat, sebum, and repeated friction in actual use, and performs comprehensive performance verification on the medical-grade antibacterial flexible circuit board of the present invention.
[0140] I. Test Conditions The sample prepared in Example 1 was immersed in artificial sweat (composition: sodium chloride 20 g / L, ammonium chloride 17.5 g / L, lactic acid 15 g / L, acetic acid 5 g / L, pH 4.7, according to ISO 3160-2 standard) and immersed in a constant temperature shaking incubator at 37°C with shaking at 100 rpm for 168 hours (7 days), with fresh artificial sweat replaced every 24 hours. After immersion, the sample was removed, gently rinsed with purified water, and dried at room temperature for 24 hours.
[0141] II. Test Results (1) Appearance inspection: The sample showed no obvious discoloration, swelling, cracks or delamination, and the aerogel layer 3 structure was intact.
[0142] (2) Antibacterial performance retention rate: The antibacterial rates of the samples after soaking were 99.2% for Staphylococcus aureus and 98.8% for Escherichia coli, respectively. Compared with before soaking (99.7% and 99.5%), the retention rates were both over 99%.
[0143] (3) Silver ion release: The concentration of silver ions in the soaking solution was detected by inductively coupled plasma mass spectrometry (ICP-MS), and the cumulative release was approximately 0.18 μg / cm³. 2 This is far below the safety limit for silver ion release from medical devices (typically <1 μg / cm³). 2 This indicates that the nano-silver is very firmly fixed in the aerogel framework and has high safety in use.
[0144] (4) Thermal insulation performance retention rate: The thermal conductivity after immersion is 0.019 W / (m·K), which is 5.6% of the initial value (0.018 W / (m·K)), which is within the acceptable range.
[0145] (5) Biocompatibility re-evaluation: The cytotoxicity test (ISO10993-5) was performed again on the soaked sample. The relative cell proliferation rate was 91%, and the cytotoxicity rating was still Grade 1, indicating that the sample still maintained good biocompatibility after being soaked in simulated body fluid.
[0146] Overall evaluation: The results of this embodiment fully verify the reliability and safety of the medical-grade antibacterial flexible circuit board provided by the present invention in actual medical application scenarios (contact with sweat and body fluids). Under the harsh conditions of simulating 7 days of continuous use, the antibacterial performance, thermal insulation performance, and biocompatibility of the sample all remain at a high level, meeting the actual use requirements of medical-grade devices.
[0147] Although this disclosure has been described in conjunction with specific embodiments thereof, many substitutions, modifications and variations of these embodiments will be apparent to those skilled in the art from the foregoing description.
[0148] One or more embodiments of this specification are intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of one or more embodiments of this specification should be included within the scope of protection of this disclosure.
Claims
1. A medical-grade antibacterial flexible circuit board, characterized in that, include: Flexible circuit board substrate (1); At least one aerogel layer is disposed on the surface of the flexible circuit board substrate (1), and the aerogel layer serves as a heat insulation separation layer. The LED beads or heating electronic components (2) are disposed on the flexible circuit board substrate (1), and the aerogel layer is disposed around or adjacent to the area where the LED beads or heating electronic components (2) are located. An antibacterial functional structure is disposed in or between the aerogel layers; The flexible circuit board has a bending region and a non-bending region, and the thickness of the aerogel layer in the bending region is less than the thickness of the aerogel layer in the non-bending region.
2. The medical-grade antibacterial flexible circuit board according to claim 1, characterized in that, The substrate (1) is made of one or more of medical-grade polyimide, liquid crystal polymer, and polyethylene terephthalate, and the biocompatibility level of the substrate (1) meets the requirements of USP Class VI or ISO 10993 standards; the matrix material of the aerogel layer is made of one or more of silica aerogel, polyimide aerogel, cellulose aerogel, and chitosan aerogel.
3. The medical-grade antibacterial flexible circuit board according to claim 1, characterized in that, The antibacterial functional structure is antibacterial particles doped in the aerogel layer. The antibacterial particles are uniformly dispersed in the gel skeleton of the aerogel during the aerogel preparation process. The antibacterial particles are selected from one or more of nano-silver particles, nano-copper particles, nano-zinc oxide particles, nano-titanium dioxide particles, and silver-loaded zeolite. The particle size of the antibacterial particles is 1-100 nm, and the doping amount is 0.1-10 wt% of the total mass of the aerogel.
4. The medical-grade antibacterial flexible circuit board according to claim 1, characterized in that, The aerogel layer includes a first aerogel layer (4) and a second aerogel layer (5), and an antibacterial particle layer (6) is disposed between the first aerogel layer (4) and the second aerogel layer (5); the antibacterial particle layer (6) is applied to the surface of the first aerogel layer (4) by atomization spraying, and the second aerogel layer (5) covers the antibacterial particle layer (6) and is bonded to the first aerogel layer (4) by medical-grade adhesive.
5. The medical-grade antibacterial flexible circuit board according to claim 1, characterized in that, The aerogel layer thickness in the bending area is 0.02–0.5 mm, and the aerogel layer thickness in the non-bending area is 0.1–2.0 mm.
6. The medical-grade antibacterial flexible circuit board according to claim 1, characterized in that, Includes the following steps: S1: Provides a flexible circuit board substrate (1); S2: At least one aerogel layer is provided on the surface of the flexible circuit board substrate (1); S3: An antibacterial functional structure is provided in or between the aerogel layers, wherein the antibacterial particles in the antibacterial functional structure meet the biocompatibility requirements of the ISO10993 series standards. S4: Control the thickness of the aerogel layer in the bending area of the flexible circuit board to be less than the thickness of the aerogel layer in the non-bending area.
7. The medical-grade antibacterial flexible circuit board according to claim 6, characterized in that, The antibacterial functional structure is fabricated in the following manner: (a) Antibacterial particles are added to the aerogel precursor solution, and after dispersion, gelation, aging, solvent replacement and drying, an aerogel layer in which antibacterial particles are uniformly doped into the gel skeleton is obtained (3); or (b) Apply a mask to the surface of the first aerogel layer (4), and spray antibacterial particles onto the exposed area using atomized spraying. After removing the mask, bond the second aerogel layer (5) to the first aerogel layer (4) with a medical-grade adhesive.
8. The medical-grade antibacterial flexible circuit board according to claim 7, characterized in that, The process parameters for atomized spraying are as follows: the distance between the spray gun (8) and the substrate is 30-150mm, the moving speed of the spray gun (8) is 500-2000mm / s, the atomization pressure is 0.1-0.6MPa, the spraying environment temperature is 15-40℃, and the relative humidity is 30-70%; the mask is a physical mask, selected from metal mask, plastic mask or composite mask, and the accuracy of the mask is controlled within ±0.1mm.
9. The medical-grade antibacterial flexible circuit board according to claim 6, characterized in that, The thickness of the aerogel layer in the bending area is controlled to be 0.02–0.5 mm, and the thickness of the aerogel layer in the non-bending area is controlled to be 0.1–2.0 mm.
10. The medical-grade antibacterial flexible circuit board according to claim 6, characterized in that: The matrix material of the aerogel layer in step (2) is selected from one or more of silica aerogel, polyimide aerogel, cellulose aerogel, and chitosan aerogel; The antibacterial particles in step (3) are selected from one or more of nano-silver particles, nano-copper particles, nano-zinc oxide particles, nano-titanium dioxide particles, and silver-loaded zeolite, and the particle size of the antibacterial particles is 1 to 100 nm.